Needed now: a world environment and development organization - Frank Biermann; Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
Global environmental policy certainly could gain strength if the management of the United Nations Environment Programme (UNEP) or of the UN Commission on Sustainable Development (CSD) were made more efficient. However, such a minimalist strategy of efficiency improvement is no panacea: it can only be an element, not the core of a new global environmental policy. Therefore, instead of merely calling for improved efficiency and coordination, in this paper a proposal is made to establish a World Environment and Development Organization (WEDO) as a new specialized agency of the United Nations. At the very least, such an Organization should integrate UNEP, the CSD and the relevant Convention Secretariats (climate, biodiversity, desertification conventions); close cooperation with the Bretton Woods institutions - the World Bank, the International Monetary Fund (IMF), the World Trade Organization (WTO) - and the existing UN specialized agencies would need to be ensured. Also, ideas are being presented on the decision-making procedures, the participation of Non-Governmental Organizations (NGOs), and on the financing of such a World Environment and Development Organization.
Keywords: 300; Internationale Umweltpolitik; Entwicklungsorganisation; Welt